(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Artificial intelligence (AI) is rapidly changing the educational landscape, opening up new horizons for the development of creativity and professional competence in the training of future teachers in the specialty A5.39 (formerly 015.39 “Vocational Education (Digital Technologies)”). Given the dynamic development of information and communication technologies (ICTs) in the modern world, it is important to study the impact of these changes on the educational process. Modern informatization of education has changed the role of the teacher as a knowledge carrier to a facilitator of learning. A modern teacher should not only be a translator of knowledge, but also an innovator, communicator, scriber, creator, tutor, coach, methodologist, and researcher. Students have access to a lot of information resources, and their role in the educational process is becoming more active. At the same time, new challenges arise due to data security and privacy. Innovative technologies, traditional, distance, online and hybrid learning models, digital platforms, interactive tools and adaptive systems contribute to a more individualized approach to the organization of the educational process. The authors of the article discuss tools and technologies that, with the support of AI (ChatGPT, Gemini, Claude, Leonardo, LearningApps, Tinkercad, etc.), including Python and Arduino robotics kits, contribute to the development of creativity and professional competence of future teachers. The use of such technologies in the educational process stimulates innovative forms of thinking, creativity, and teamwork among students majoring in A5.39. AI libraries (TensorFlow, PyTorch, etc.) are allow future teachers to dive into the world of AI without requiring deep programming knowledge. Integrating AI, Python, and Arduino into teacher education stimulates creativity, develops professional competencies, and prepares future teachers for the challenges of modern education. Hybrid learning models, where technological tools are combined with pedagogical innovations, form competent, creative and self-confident professionals capable of working in the digital age.